The Influence of Local Original Income, Unemployment and Gini Ratio on Poverty Levels in West Nusa Tenggara Province 2019-2023 - Hary Anggara; Siti Sriningsih; Ahmad Zaenal Wafik (Indonesian Development Economics and Localities, 2025)
This study aims to analyze the Influence of Local Original Income (X1) Unemployment (X2) and Gini Ratio on Poverty Level in West Nusa Tenggara Province in 2019-2023. The data used are secondary data obtained from the Central Statistics Agency (BPS) of NTB Province, and analyzed using the panel data regression method. The results of the study partially show that local original income (X1) has a positive and insignificant effect on the poverty level (Y) of West Nusa Tenggara Province in 2019-2023. unemployment (X2) has a negative and significant effect on the poverty level (Y) of West Nusa Tenggara Province in 2019-2023 and the Gini ratio (X3) has a positive and significant effect on the poverty level (Y). While simultaneously the variables of local original income (X1) unemployment (X2) and the Gini ratio simultaneously affect the poverty level (Y) of West Nusa Tenggara Province in 2019-2023.